ANALISIS PENERAPAN ETIKA BISNIS ISLAM DAN SYARIAH MARKETING BMT MEKAR DA'WAH SERPONG MENURUT FATWA DSN-MUI NO. 04/DSN-MUI/IV/2000 - Fatma Yeni; Endah Lestari (Universitas Muhammadiyah Prof Dr Hamka, 2020)
This study aims to determine whether BMT Mekar Da'wah Serpong has implemented Islamic business ethics and sharia marketing in accordance with the theory of Islamic law. The research method is qualitative using interview techniques, library research and internet searching. Then the data obtained were analyzed using descriptive analysis. The results showed that BMT Mekar Da'wah has implemented Islamic business ethics in accordance with the existing principles of Islamic business ethics. In its business activities, BMT Mekar Da'wah is free from usury, can balance economic and social activities, gives members the freedom to choose its products, is responsible to its members and social activities funded by baitul maal, and honesty is applied to employees. BMT. Then, BMT Mekar Da'wah has implemented sharia marketing in accordance with the existing characteristics of sharia marketing. BMT Mekar Da'wah has instilled religious values